The primary stability of the femoral component in cemented single and twin peg Oxford unicompartmental knee arthroplasty under adverse conditions. Issue 2 (7th February 2022) - Eckert, Johannes Adrian; Bitsch, Rudi G.; Sonntag, Robert; Reiner, Tobias; Schwarze, Martin; Jaeger, Sebastian
Abstract : Aims: The cemented Oxford unicompartmental knee arthroplasty (OUKA) features two variants: single and twin peg OUKA. The purpose of this study was to assess the stability of both variants in a worst-case scenario of bone defects and suboptimal cementation. Methods: Single and twin pegs were implanted randomly allocated in 12 pairs of human fresh-frozen femora. We generated 5° bone defects at the posterior condyle. Relative movement was simulated using a servohydraulic pulser, and analyzed at 70°/115° knee flexion. Relative movement was surveyed at seven points of measurement on implant and bone, using an optic system. Results: At the main fixation zone, the twin peg shows less relative movement at 70°/115°. At the transition zone, relative movements are smaller for the single peg for both angles. The single peg shows higher compression at 70° flexion, whereas the twin peg design shows higher compression at 115°. X-displacement is significantly higher for the single peg at 115°. Conclusion: Bony defects should be avoided in OUKA. The twin peg shows high resilience against push-out force and should be preferred over the single peg. Cite this article: Bone Joint Res  2022;11(2):82–90.